2020
DOI: 10.1007/978-3-030-65847-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Reusable FAIR Implementation Profiles as Accelerators of FAIR Convergence

Abstract: Powerful incentives are driving the adoption of FAIR practices among a broad cross-section of stakeholders. This adoption process must factor in numerous considerations regarding the use of both domain-specific and infrastructural resources. These considerations must be made for each of the FAIR Guiding Principles and include supra-domain objectives such as the maximum reuse of existing resources (i.e., minimised reinvention of the wheel) or maximum interoperation with existing FAIR data and services. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…A first step toward achieving this is to ensure that there is convergence on FAIR implementations in the healthcare domain. Community-specific FAIR Implementation Profiles [13] can drive this convergence.…”
Section: Discussionmentioning
confidence: 99%
“…A first step toward achieving this is to ensure that there is convergence on FAIR implementations in the healthcare domain. Community-specific FAIR Implementation Profiles [13] can drive this convergence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, FAIR guiding principles spotlight the need to develop the capacities of computational systems to manage the monitoring, collection, processing, and stewardship of the digital resources to be evaluated, with a minimum of human interventions, due to the “big data” and “cloud computing” revolutions inducing an increase of data volume, velocity, and variability in the health and medicine arena. 11 To this end, an integrative literature review 12 13 was conducted to extract instances of the need—or of the eventual already existing deployment, explicitly reported or not—of FAIR principles with FAIR-enabling digital resources-like 14 (e.g., datasets, metadata, code, protocols, compute resources, data policies, identifier mechanisms, standards) for each of the three layers featured by the ODH framework. The review was processed by seeking for publications, on medical and engineering search engines (e.g., PubMed, IEEE Xplore, Science Direct), totally or partially related to the combinations of, at least, one FAIR principle and, at least, one of the ODH “steering wheel” features, for example, keys, perspectives, or dimensions (or synonyms).…”
Section: Methodsmentioning
confidence: 99%
“…The M4M facilitators have also demonstrated that their format can be replicated by other facilitators who are trained in the approach. GO FAIR construes M4M workshops as the vehicle for creating key elements of what it calls FAIR Implementation Profiles (FIPs) 41 -an intentionally generic term for the set of design choices that a given scientific community makes to implement the FAIR Guiding Principles. These design choices largely boil down to decisions about standards.…”
Section: Methodsmentioning
confidence: 99%